RISKS AND SAFETY OF USING NANOTECHNOLOGIES OF FOOD PRODUCTS: A REVIEW - N. A. Gorbunova; E. K. Tunieva (Теория и практика переработки мяса)
The problem of healthy and quality nutrition has a global character. The modern development of technologies including nanotechnologies allowed obtaining materials with unique properties, which began to be actively used in food industry and agriculturebut, at the same time, require thorough investigation of their properties and effects on the human body and environment. The paper demonstrates the main directions of the nanotechnology use in the agricultural production and food industry, examines the safetyproblems and risks occurred when using nanotechnologies in food industry with account for insufficient research on the influence of food nanotechnologies on human health and environmental ecology, and presents the normative and methodical base of the RussianFederation for assurance of safe consumption of food products produced from nanomaterials.